Inspired by struggle: A personal journey to global precision brain health - Agustin Ibanez (iScience)
Dr. Agustin Ibanez joins iScience editor Maryam Fard to discuss his personal journey in brain health research. He advocates for integrating diversity in neurodegeneration studies, crucial for understanding conditions like dementia. He founded ReDLat and BrainLat, advancing research across Latin America and empowering underrepresented voices. This inspiring discussion showcases his commitment to fostering interdisciplinary approaches to drive global brain health progress. Dr. Ibanez is also the Guest Editor of iScience’s Special Issue: “Transdisciplinary approaches to arts and health: Integrating creative practice in clinical and public health contexts.”